"Corporate Social Responsibility” (CSR) sebagai Aktivitas “Social Marketing Public Relations" - Neni Yulianita (MediaTor (Jurnal Komunikasi), 2008)
Corporate Social Responsibility (CSR) nowadays becomes indicator of corporate achievement. CSR activities, which commonly defined as corporate efforts to increase community and stakeholder life quality, open up relations between corporate and community. In turn, CSR would maintain good image and give posing the positive publicity toward corporate image. This article explores CSR activities as implied on PR marketing in some corporates.